The maze of bones - Riordan, Rick. (The 39 clues ;, 2008)
When their beloved aunt--matriarch of the world's most powerful family--dies, orphaned siblings Amy and Dan Cahill compete with less honorable Cahill descendants in a race around the world to find cryptic clues to a mysterious fortune. Includes game cards which the reader may use to play an online version of the treasure hunt.